Potential for Recombinant ADAMTS13 as an Effective Therapy for Acquired Thrombotic Thrombocytopenic Purpura. Issue 11 (November 2015) - Tersteeg, Claudia; Schiviz, Alexandra; De Meyer, Simon F.; Plaimauer, Barbara; Scheiflinger, Friedrich; Rottensteiner, Hanspeter; Vanhoorelbeke, Karen
Abstract : Objective—: The metalloprotease ADAMTS13 (a disintegrin and metalloproteinase with a thrombospondin type 1 motif, member 13) regulates the size of von Willebrand factor multimers. A deficiency in ADAMTS13 activity is associated with the life-threatening disease thrombotic thrombocytopenic purpura (TTP). The vast majority of patients have acquired TTP, where circulating anti-ADAMTS13 autoantibodies are causative for the decreased ADAMTS13 activity. Current treatment consists of plasma exchange, but improved therapies are highly warranted. Approach and Results—: We have developed a new rat model mimicking various aspects of acquired TTP to investigate the therapeutic efficacy of human recombinant ADAMTS13. A polyclonal antibody against ADAMTS13 completely blocked endogenous rat ADAMTS13 activity in Sprague–Dawley rats. When TTP was triggered using recombinant von Willebrand factor, the animals displayed severe TTP-like symptoms, such as thrombocytopenia, hemolytic anemia, and von Willebrand factor–rich thrombi in the kidneys and brain. Subsequent injection of 400, 800, or 1600 U/kg recombinant ADAMTS13 prevented full development of these symptoms. Analysis of plasma samples confirmed that recombinant ADAMTS13 was able to override circulating anti-ADAMTS13 inhibitory antibodies, resulting in restoration of ADAMTS13 activity and degradation of ultralarge von Willebrand factor multimers. Conclusions—: Recombinant ADAMTS13 was shown to be effective in averting severe acquired TTP-like symptoms in rats and holds promising value for the treatment of this severe and life-threatening disease in humans. Abstract : Supplemental Digital Content is available in the text.